HUKUM SEBAGAI PENYOKONG KEBAHAGIAAN: KONSEP UTILITARIANISME JEREMY BENTHAM DALAM KONTEKS MODERN - Pertiwi, Kunti Tri; Roemansyah, Deddy (PRODI HUKUM TATANEGARA, 2024)
Law has an important role in realizing people's happiness as one of the main goals of human life. The theory of utilitarianism developed by Jeremy Bentham places happiness as a basic principle that must be achieved through law. According to Bentham, a good law is a law that maximizes happiness for the greatest number of people, taking into account social benefits. In this context, law not only functions as a tool for upholding justice, but also as a means to reduce suffering and facilitate collective welfare. This research examines Bentham's views on the relationship between law and happiness, the role of law in creating prosperity, and the challenges of applying the principles of utilitarianism in the modern legal system. With a normative approach, this research explores how law can be an instrument for realizing social happiness through protecting human rights, regulating economic and social relations, and promoting community welfare. The results show that although utilitarianism provides a clear framework for achieving the greatest happiness, its application faces criticism regarding the disregard of individual rights for the benefit of the majority, as well as the difficulty in measuring happiness objectively. Therefore, a balance is needed between the principles of utility and social justice so that law can truly support happiness.